Work-Related Injury among Welders Working in Metal Workshops of Johan Pahlawan Districts, Aceh Barat - Danvil Nabela; Dian Fera; Susy Sriwahyuni; Maiza Duana (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
A work accident is an unexpected event or event that can cause harm to the work process, causing human and property casualties. Therefore prevention must be carried out by reducing hazard factors that lead to accidents, taking into account unsafe action, unsafe conditions, and safety management: system, the worker's mental condition, and the worker's physical condition. The method in this research is descriptive-analytic with a cross-sectional design. We took a sample of 45 respondents. The sampling technique is the total population. We performed a logistic regression test using the Stata 14 application in this study. Results study could concluded there is a significant relationship between the use of PPE ( P-value = 0.001 , OR = 14.14, CI = 2.86 – 60.21 ) and unsafe acts (P-value = 0.015, OR = 5.5, CI = 1.39 – 21.71) with work accidents in the District Johan the Hero of West Aceh Regency in 2022.  We suggest that welding workshop owners provide protective equipment for their workers to create comfort, work safety, and reduce potential hazards while working. We also recommend using n methods to increase self-confidence so that you can focus and be careful when welding.